APLIKASI SENSOR GAS UNTUK SISTEM PERINGATAN DINI DETEKSI GAS AMONIAK - Eva Inaiyah Agustin; Winarno; Dandung Wahyu Amrulloh; Septilia Regita Cahyani (J-Innovation, 2018)
Gas leakage is a major problem in the industrial sector, especially for dangerous gases such as ammonia (NH3). This automatic gas detection device is made to provide information about the levels of ammonia gas in the event of a gas leak and provide an early warning. The gas sensor used is a type of semiconductor that is MQ-135 which is stable and has high sensitivity. Gas evaporation method was performed to compare betweenstandard ppm (calculation) with measurable ppm. The analog voltage coming out of the sensor is converted to the ADC value by the ATMega 328 microcontroller.The transfer equation functions y = 153.7ln (x) + 223.11 obtained from the relationship between ppm value and ADC. This equation is used as a reference for detecting gas in accordance with sensor characteristics. A warning alarm will sound when the ammonia gas levels more than 100 ppm.